Analisis Perbandingan Kinerja Keuangan Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia (Bei) Sebelum Dan Sesudah Adopsi Ifrs Tahun 2010-2013 - Rozy, Alfan Baharuddin Ar; , Dr.Zulfikar, SE,M.Si (2016)
IFRS stands for International Financial Reporting Standards constituting Standard Financial Accounting Statement (PSAK) used as agreed global accounting standard.This aimed to examine whether or not there is an effect of IFRS application on the financial performance of manufacturing companies enlisted in Indonesia Stock Exchange. This study employed Paired Sample t-test. The population of research was 50 manufacturing companies enlisted in Indonesia Stock Exchange during 2010-2013. The sample of research was determined using purposive sampling. The processing was conducted by grouping data into and after before IFRS application.From the result of research, it could be concluded that financial performance of manufacturing companies did not affect significantly the application of IFRS because out of 7 ratio, only two had significance effect on; Debt to Equity Ratio and Net Profit Margin, the sample was tested using paired sample test.